Pendidikan Islam dan Pengembangan Kurikulum Integratif - Bimo Hidayatullah; Dyas Pramesthi Agustin; Ithqiyya Izzat Bilqisy (Jurnal Pendidikan Guru Profesional, 2026)
The dichotomy between religious and general sciences remains a chronic structural obstacle in realizing holistic and competitive Islamic education in the 21st century. This phenomenon not only impacts institutional fragmentation but also creates an identity crisis among students who struggle to integrate spiritual values with the demands of modern science. This study aims to deeply analyze the philosophical foundations of integrative curriculum development and synthesize its implementation models based on a comprehensive literature review of twenty-five primary academic documents. The research method employs a qualitative library research approach with critical and interdisciplinary content analysis techniques. Data were collected through identification, selection, and extraction of ideas from journals, books, and proceedings covering dimensions of ontology, epistemology, axiology, educational history, to contemporary case studies. Key findings indicate that authentic curriculum integration requires a strong Tawhid foundation not merely as a slogan, but as a unifying paradigm that synergizes naqli and aqli sources of knowledge. This study reveals that past integration failures are often caused by a lack of understanding of diverse philosophical typologies, limited pedagogical competence of teachers, and the reduction of integration to a merely symbolic level. Furthermore, this research finds that integration models in Indonesia vary widely, influenced by the historical dynamics of the Pan-Islamism movement, national thinkers' ideas, and responses to globalization. It is concluded that effective integrative curriculum development demands a total reconstruction of the educator's paradigm, a holistic evaluation design accommodating all human dimensions, and policies that are flexible yet firmly rooted in Islamic values.